Problem Behaviors in Maltreated Children and Youth: Influential Child, Peer, and Caregiver Characteristics, 1999-2000 (United States) - Wall, Ariana E. ([Verlag nicht ermittelbar], 2005)
This project examined the problem behaviors of maltreated children and adolescents and the predictors of changes in behavior over an 18-month period. Problem behaviors included aggression, delinquency, risky sexual practices, substance abuse, and suicidal behaviors. The project used data from the National Survey of Child and Adolescent Well-Being (NSCAW), a national probability survey of children assessed following a child maltreatment report. This collection consists of SAS code used to produce subsets of the NSCAW data and the analyses for three chapters of the project's final report. Chapter 2 examined aggression and changes in behavior over 18 months for children aged six to ten years at the time of the baseline interview. Chapter 3 examined self-reported delinquency and caregiver-reported aggressive and delinquent behavior and changes in behavior over 18 months for youth aged 11 to 15 years at the time of the baseline interview. Chapter 4 examined risky behavior changes (risky sexual behavior, substance abuse, and suicidal risk behavior) over 18 months for youth aged 11 to 15 years at the time of the baseline interview.